Trends in utilization of agro-industrial byproducts for production of bacteriocins and their biopreservative applications. (3rd March 2016) - Bali, Vandana; Panesar, Parmjit S.; Bera, Manab B.
Abstract: Bacteriocins are proteinaceous, ribosomally synthesized bio-molecules having major roles in food preservation due to their antimicrobial action against food spoilage microorganisms. These have gained importance in the last decades because of increasing interest in natural products and their applications in the field of biopreservation, pharmaceutical, aquaculture, livestock, etc. Their production is quite expensive which includes the cost of synthetic media and downstream processing of which 30% of the total production cost relies on synthetic media and nutritional supplements used for growth of microorganisms. The low cost agro-industrial by-products, rich in nutritional supplements, can act as a good substitute for high valued synthetic media. This review provides comprehensive information on the use of cost effective, renewable agro-industrial by-products as substrates for the production of bacteriocins and their application in food as biopreservatives.